2019
DOI: 10.14309/ajg.0000000000000446
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Sex Hormone Levels and Risk of Esophageal Adenocarcinoma in a Prospective Study in Men

Abstract: Objectives: Sex hormones have been hypothesized to explain the strong male predominance in esophageal adenocarcinoma, but evidence is needed. This study examined how circulating sex hormone levels influence future risk of esophageal adenocarcinoma. Methods:This case-control study was nested in a prospective Norwegian cohort (Janus Serum Bank Cohort), including 244 male esophageal adenocarcinoma patients and 244 male agematched control participants. Associations between pre-diagnostic circulating levels of 12 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…To date, there have been just two prospective studies of prediagnostic circulating sex hormones and risk of upper gastrointestinal cancers. Combined, these studies provide evidence for an inverse association between endogenous circulating testosterone and esophageal adenocarcinoma risk (13,14), but there was less evidence for inverse associations of estradiol, luteinizing hormone (LH), and dehydroepiandrosterone (DHEA) with esophageal adenocarcinoma (15). Meanwhile, no study has specifically investigated risk of esophageal squamous cell carcinoma or gastric cancer with respect to prediagnostic circulating sex hormones.…”
Section: Introductionmentioning
confidence: 99%
“…To date, there have been just two prospective studies of prediagnostic circulating sex hormones and risk of upper gastrointestinal cancers. Combined, these studies provide evidence for an inverse association between endogenous circulating testosterone and esophageal adenocarcinoma risk (13,14), but there was less evidence for inverse associations of estradiol, luteinizing hormone (LH), and dehydroepiandrosterone (DHEA) with esophageal adenocarcinoma (15). Meanwhile, no study has specifically investigated risk of esophageal squamous cell carcinoma or gastric cancer with respect to prediagnostic circulating sex hormones.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22] We evaluated the following 12 sex hormone measures in serum samples: sex hormone-binding globulin (SHBG); the nine steroid sex hormones dehydroepiandrosterone sulfate, follicle-stimulating hormone (FSH), luteinizing hormone, prolactin, testosterone, 17-OH-progesterone, progesterone, estradiol and androstenedione; and finally calculated free testosterone index (testosterone × 10/SHBG) and testosterone:estradiol ratio. These hormone measures cover key points in the biosynthesis of sex hormones, 7,11,23 and are at detectable levels in serum in men with the available analytic methods.…”
Section: Hormone Level Exposuresmentioning
confidence: 99%
“…This striking male predominance may be explained by the differences in endogenous sex hormonal levels between the sexes 1,6 . Recent studies have reported associations between circulating sex hormone levels and the risk of developing EAC and its precursor Barrett's esophagus 7‐11 . Any procarcinogenic or anticarcinogenic effects of certain sex hormones could potentially influence treatment efficacy and risk of tumor recurrence after treatment of EAC.…”
Section: Introductionmentioning
confidence: 99%
“…Testosterone plays a critical role in the metabolism of proteins, carbohydrates, and fat; therefore, de ciency can contribute to the development of functional disorders throughout the body [16]. Previous studies have reported the high incidence of testosterone de ciency among critically ill patients with condition such as myocardial infarction, acute respiratory failure, and esophageal adenocarcinoma [17][18][19]. Recent data have demonstrated that, among men with end-stage liver disease, low testosterone is associated with an increased risk of mortality regardless of the etiology of disease [20][21][22].…”
Section: Introductionmentioning
confidence: 99%